The Missionary and the Anthropologist: The Intellectual Friendship and Scientific Collaboration of the Reverend John Roscoe (CMS) and James G. Frazer, 1896–1932 - (:unkn) unknown (My University, 2016)
A rapidly expanding field, the study of the interactions between missions and sciences, and most notably missions and anthropology, has opened up new ways of examining the scholarly work of missionaries and their extra-apostolic activities. Historians of missions are drawn to archival materials that had been previously overlooked, such as the contributions of missionaries to scientific journals, or their correspondence with figures that worked outside of missionary circles. This article focuses on one such correspondence between the social anthropologist James George Frazer and the Revd John Roscoe, who worked for the Church Missionary Society in Uganda between 1889 and 1911. Not only was Roscoe a mine of information on Central African tribes for Frazer, he was also, after he retired from the CMS, a keen student of anthropology who devoted the second part of his life to anthropological ventures: he wrote the first ethnological account on the Baganda, contributed to enriching the Cambridge Museum of Archaeology and Anthropology's collections of Central African relics and artefacts, helped set up training courses in anthropology for prospective missionaries and led an anthropological expedition. His work, and his long correspondence with Frazer, bears the mark of the renowned anthropologist's theories on totemism, a notion that was at the core of the international anthropological scene in the late-Victorian and Edwardian period.
Keywords: African Research